Influence of statin therapy at time of stroke onset on functional outcome among patients with atrial fibrillation. (15th January 2017) - Ko, Darae; Thigpen, Jonathan L.; Otis, James A.; Forster, Kristen; Henault, Lori; Quinn, Emily; Tripodis, Yorghos; Berger, Peter B.; Limdi, Nita; Hylek, Elaine M.
Abstract: Background: Statin pretreatment has been associated with reduced infarct volume in nonlacunar strokes. The effect of statins on functional outcomes of strokes related to atrial fibrillation (AF) is unknown. We aimed to define the influence of prestroke statin use on functional outcome in AF. Methods: We assembled a cohort of consecutive ischemic stroke patients from 2006 to 2010. All patients underwent CT or MRI and were adjudicated by site investigators. AF was confirmed by electrocardiogram in 100% of patients. Site neurologists blinded to the study hypothesis affirmed the type of stroke and assessed the severity of disability at the time of hospital discharge. The frequency of death at 30-days was calculated. Results: Ischemic stroke ( n  = 1030) resulted in a severe neurological deficit or death (modified Rankin scale ≥ 4) at 30 days in 711 patients (69%). Using multivariable logistic regression models adjusting for factors associated with statin treatment and factors associated with functional outcome, prestroke statin use was associated with a 32% reduction in frequency of severe stroke (odds ratio [OR], 0.68; 95% confidence interval [CI], 0.50–0.92; P  = 0.011). Other independent factors associated with severe stroke included older age, female sex, non-White race, diabetes mellitus, prior ischemic stroke, prior venous thromboembolism, and dementia. Conclusion: Ischemic strokes in AF are associated with high mortality and morbidity. Statin use at time of stroke onset among patients with AF was associated in this study with less severe stroke and warrant validation.